(untitled) (ACTUALITĂŢI ŞI PERSPECTIVE ÎN DOMENIUL MAŞINILOR ELECTRICE (ELECTRIC MACHINES, MATERIALS AND DRIVES - PRESENT AND TRENDS, 2024)
This work is a review of some research results on some new topologies of electrical machines proposed to be used in propulsion systems of electric vehicles. These new topologies have been presented at the International Electric Machines & Drives Conference, May 12-15, 2019, San Diego, California. There are discussed various new topologies of permanent magnet electrical machines like: electrical machines with alternating poles or with consecvent poles, in surface or in spoke topology, with distributed or concentrated windings, with the rare earth magnets or with a mix of rare earth magnets and ferite magnets, with one or with two stators, with radial or with axial magnetic field. Also, there are discussed various reluctance and hybrid topologies used for high speed electrical machines. Other discussed issues are related to speed domain extension using various windings connection schemes for induction motors and for switched synchronous reluctance motors. Special topologies which can improve air or water cooling of electrical machines are, also, discussed.